A function block based cyber-physical production system for physical human–robot interaction. (July 2018) - Yao, Bitao; Zhou, Zude; Wang, Lihui; Xu, Wenjun; Yan, Junwei; Liu, Quan
Abstract: Human–robot collaboration (HRC) is becoming a trend in manufacturing industry. However, the dramatic changes of requirements from the market put a higher demand for the flexibility of manufacturing systems. Cyber-Physical Production System (CPPS) which offers benefits of autonomy, self-organisation, and interoperability can be adopted to increase the flexibility of manufacturing systems. IEC 61499 (International Electrotechnical Commission) function blocks (FBs) are modularised and reusable software components for distributed industrial control. It is a suitable technology to realise a CPPS. Therefore, CPPS and FBs can be combined to realise the HRC system. This paper proposes a framework and the implementation method of IEC 61499 FB based CPPS for physical human–robot interaction (pHRI) which is type of HRC. An industrial robot based CPPS for pHRI is decomposed into modularised FBs that can be networked to fulfil manufacturing tasks. An energy consumption FB based on a novel empirical energy consumption model is also added to the system for energy consumption monitoring of the Robot. An assembly case is used to demonstrate the feasibility of the proposed system. Results show that the FB based CPPS for pHRI possesses the potential capability for HRC based assembly. The future work is also discussed.